Hubungan Kualitas Pelayanan Kesehatan Dengan Kepuasan Pasien Rawat Inap di FKTP: Literature Review - Dina Ayu Mashita; Ervina Racmawati; Atma Deharja; Efri Tri Ardianto (Politeknik Negeri Jember, 2022)
The quality of Puskesmas services was an important factor in the utilization of health services. Patient satisfaction was an important measure of the effectiveness of health care providers to fulfill patient needs and expectations. The purpose of this research is to determine the relation between the quality of health services (tangible, reliability, responsiveness, assurance, empathy) and the satisfaction of inpatients at first-level health facilities. The method used is a literature review by analyzing 10 articles from various sources. Based on the results of the literature study from various studies obtained, the researcher stated that 3 articles that the overall quality of health services (tangible, reliability, responsiveness, assurance, empathy) have a significant relationship with patient satisfaction. A total of 6 literatures show that the tangible dimensions are related and 1 literature shows that there is no relationship. There are 4 dimensions of reliability that show a relationship and 3 literature that show no relationship. The responsiveness dimension consists of 4 literature showing a relationship and 3 literature that is not related. The assurance dimension consists of 3 literature showing a relationship and 4 literature that is not related to patient satisfaction. The empathy dimension consists of 5 literatures that show a relationship and 2 literature that show no relationship with patient satisfaction. The assurance dimension is considered is not good so that it has no relationship with patient satisfaction. There are literatures that only writes the correlation test results without explaining the situation or facts found in first-level health facilities.